Kemampuan Menganalisis Struktur Fisik dan Struktur Batin Puisi Siswa Kelas X SMA Muhammadiyah 3 Kabupaten Pulau Morotai - Sartika Samad (Peneliti.net, 2026)
This study aims to a) describe students' abilities in analyzing physical elements, namely diction, imagery, and concrete words in Chairil Anwar's poem